2002
DOI: 10.21273/hortsci.37.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Toxicity in Watermelon as Affected by Lime and Compost Amended to a Hawaiian Acid Oxisol

Abstract: Manganese (Mn) toxicity in crops is a serious problem in Hawaii, especially Kauai and Oahu, where most soils are highly weathered. To devise a management strategy to control Mn toxicity, a greenhouse experiment was conducted on an acid (pH 4.4) Oxisol (Wahiawa series) having 15g·kg-1 total Mn. Factorial combinations of lime (0, 2.0, and 4.0 g·kg-1 CaCO3) and two composts (made from chicken manure and from sewage sludge at 0, 5, and 10 g·kg<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Indeed, these soils (which are referred to as Ultisol and Oxisol) are known to contain high concentrations of Al (Vityakon and Seripong, 1989) that can be reduced by biochar addition through: i) the increase of soil pH and ii) the input of organic material which decreases the part of exchangeable Al through adsorption processes and decreases the toxicity of Al through chelation with organic compounds from biochars (Haynes and Mokolobate, 2001;Hue et al, 1986). The decrease of the Mn content could be attributed to the increase in Ca availability, which reduced MneCa competition for plant uptake (Hue and Mai, 2002). Another proof of the beneficial aspects of biochar was given by Olmo et al (2014), who observed increases in fine root proliferation and crop development after soil amendment by olive tree pruning biochar.…”
Section: Enhancement Of Agronomic Potentialitiesmentioning
confidence: 99%
“…Indeed, these soils (which are referred to as Ultisol and Oxisol) are known to contain high concentrations of Al (Vityakon and Seripong, 1989) that can be reduced by biochar addition through: i) the increase of soil pH and ii) the input of organic material which decreases the part of exchangeable Al through adsorption processes and decreases the toxicity of Al through chelation with organic compounds from biochars (Haynes and Mokolobate, 2001;Hue et al, 1986). The decrease of the Mn content could be attributed to the increase in Ca availability, which reduced MneCa competition for plant uptake (Hue and Mai, 2002). Another proof of the beneficial aspects of biochar was given by Olmo et al (2014), who observed increases in fine root proliferation and crop development after soil amendment by olive tree pruning biochar.…”
Section: Enhancement Of Agronomic Potentialitiesmentioning
confidence: 99%
“…As soils in southwestern Indiana are often acidic, Mn 2+ toxicity could contribute to inhibition of watermelon root growth. Acid pH increases Mn 2+ solubility and phytoavailability which results in toxicity (Hue and Mai, 2002). Mn 2+ toxicity is characterized by competition with Mg 2+ uptake and utilization: Mn 2+ can compete with cation uptake, displace Mg 2+ enzyme co-factors, displace Ca 2+ in cell membranes and enhance axilliary shoot growth (Marschner, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of AWC soil amendment and CTB foliar spray were particularly evident on the qualitative intrinsic parameters of the fruits rather than on agronomic traits while, MWC decreased overall parametric set. Few previous studies concerning the use of the compost to grow plants of this species highlighted a low sensitive yield response to compost amendment [33], as well as more different effects depending by soil type and compost property [34]. Likely, this particular behaviour is due to the continue struggle between compost, promoting growth factors, and the appearance of allelopathy to which watermelon is reported to be very sensible [35] [36].…”
Section: Discussionmentioning
confidence: 97%